Advances in Molecular Breeding of Vegetable Crops (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Vegetable crops provide valuable minerals and vitamins that are indispensible for human health. Scientists have been working on the genetics of vegetable crops, deciphering the molecular bases of agronomically important traits. These genetic bases and variations in vegetable traits will greatly facilitate vegetable genetic improvement. Therefore, the genes of and genetic research on vegetable crops are of great importance. This Special Issue is a collection of 13 important research papers addressing the genes, genetics, and breeding of major vegetable crops. In the present book, the authors described the genes and QTLs responsible for stress tolerance, disease resistance, vegetable yield, and quality. The 13 research papers cover germplasm enhancement and evaluation, QTL mapping, gene isolation, marker development, and gene expression as well as gene editing in a wide range of vegetable species, including broccoli, pepper, eggplant, onion, and Cucurbita species. Readers from all over the globe are expected to greatly benefit from this Special Issue collection regarding their own work and the goal of improving breeding efficiency with molecular breeding to generate environment-adaptive, high-yield, and high-quality vegetable crops with which to feed the global population of 9.7 billion in an extreme climate by 2050.